2009
DOI: 10.1002/hep.23075
|View full text |Cite
|
Sign up to set email alerts
|

Distinct kinetics and dynamics of cross-presentation in liver sinusoidal endothelial cells compared to dendritic cells

Abstract: Cross-presentation is an important function of immune competent cells, such as dendritic cells (DCs), macrophages, and an organ-resident liver cell population, i.e., liver sinusoidal endothelial cells (LSECs). Here, we characterize in direct comparison to DCs the distinct dynamics and kinetics of cross-presentation employed by LSECs, which promote tolerance induction in CD8 T cells. We found that LSECs were as competent in cross-presenting circulating soluble antigen ex vivo as DCs at a per-cell basis. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 35 publications
(56 reference statements)
4
49
0
Order By: Relevance
“…4) showing OVA colocalization with the clathrin H chain in LECs at early times after exposure. Similar observations were made with LSECs (14) and are consistent with early endosome colocalization observed in BMDCs (46). At later time points, OVA was found in LAMP-1 + vesicles, supporting the data showing chloroquine inhibition of Ag cross-presentation (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…4) showing OVA colocalization with the clathrin H chain in LECs at early times after exposure. Similar observations were made with LSECs (14) and are consistent with early endosome colocalization observed in BMDCs (46). At later time points, OVA was found in LAMP-1 + vesicles, supporting the data showing chloroquine inhibition of Ag cross-presentation (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 89%
“…As described for other murine stromal cells, such as LSECs (14,48), aortic endothelial cells (49), and thymic stromal cells (50), we found that the TAP1-dependent transport of cytoplasmic peptides into the ER (Fig. 2D) and ER-golgi trafficking (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite this, our experiments impressively demonstrate that a single tail vein injection of mCD105-LV Epo was sufficient to increase erythropoietin levels in the circulation to 25-fold above physiological values. Importantly, dose-response analysis revealed no toxicity in treated animals, and liver enzyme values remained unchanged even at a particle dose (15 mg p24), similar to that which substantially raised liver transaminase levels for VSV-G-LV (25 mg p24) 43 (supplemental Figure 5). These and the resulting high hematocrit values remained constant over several weeks in immunocompetent mice also, indicating that no cellular immune response against the transduced cells was mounted.…”
Section: Discussionmentioning
confidence: 55%
“…This led us to investigate whether the numbers of peptideloaded MHC-I molecules and thus the strength of TCR signaling influenced tolerogenic T cell priming by cross-presenting LSECs. LSECs represent a unique liver-resident cell population that is even more potent in cross-presentation than CD8a + splenic DCs when compared at a per-cell basis (19). Cross-presentation of soluble Ag by LSECs in vivo is functional and sufficient to cause Ag-specific retention of circulating naive CD8 T cells to the liver (5).…”
Section: Discussionmentioning
confidence: 99%